Explanations for the observed increase in fast electron penetration in laser shock compressed materials - Batani, D; Davies, JR; Bernardinello, A; Pisani, F; Koenig, M; Hall, T; Ellwi, S; Norreys, P; Rose, S; Djaoui, A; Neely, D (2000)
We analyze recent experimental results on the increase of fast electron penetration in shock compressed plastic [Phys. Rev. Lett. 81, 1003 (1998)]. It is explained by a combination of stopping power and electric field effects, which appear to be important even at laser intensities as low as 10-16 W cm-2. An important conclusion is that fast electron induced heating must be taken into account, changing the properties of the material in which the fast electrons propagate. In insulators this leads to a rapid insulator to conductor phase transition.